ENERGY AND ECONOMIC ANALYSIS OF BIOGAS POWER PLANT FROM MUNICIPAL SOLID WASTE IN INDONESIA - Aditia Aulia; Hadi Wahyudi; Edy Susanto (Jurnal Poli-Teknologi, 2021)
Indonesia is the fourth most populous country with a population of more than 270 million people and is expected to continue to increase. The increasing population has an effect on increasing municipal solid waste (MSW) generation and energy demand. Waste-to-energy (WTE) can be a solution to these two problems. This article will discuss two types of waste-to-energy technology, namely anaerobic digestion and landfill gas recovery. The study began by conducting kinetic modeling on the two technologies to determine the potential of biogas energy produced from municipal waste in Indonesia, the case study applied was Yogyakarta. Then a feasibility study was carried out to find out whether these two technologies are possible to be applied in Indonesia in terms of various aspects such as initial capital costs, operating and maintenance costs, and waste processing service costs. At the end of the study, it was found that biogas power plant with both technology bases was economically feasible. Landfill gas recovery is more attractive because it has a smaller capital and a higher IRR of 22%. The scenario using anaerobic digestion requires a larger capital than the previous scenario and has a lower IRR value of 14%. Keywords: Biogas, Municipal Solid Waste (MSW), Kinetic modeling, Waste-to-energy (WTE), Feasibility study.